Verbal predication negation in Dawurotsuwa - Aklilu Abera Naba (Cogent Arts & Humanities)
This paper presents an analysis of the verbal negation of declarative main clauses in Dawurotsuwa. This study aims to describe verbal negation in Dawurotsuwa, a language that is scarcely described. Having prepared phrases and sentences for elicitation, which are appropriate and purposefully fitting to the verbal predication negation in English and Amharic, the data were collected from native speakers of Dawurotsuwa. The finding shows that the language suffixes negative markers to the root. Verbal negation in main clauses is formed by suffixing the morphemes -kk-/-nn- to the verb along with other inflectional suffixes, such as person, number, and aspect. The negative morpheme -kk- is used for all persons except 3SG.M. The morpheme -nn- is used for 3SG.M and infinite verb forms. Negation in Dawurotsuwa is asymmetric, in which the structural difference between affirmative and corresponding negative goes beyond the mere existence of the negative marker. The negative and perfective aspect marker co-occur together though the perfective aspect marker is substituted by another marker in the negative. The imperfective aspect is not marked in the language. The language emphasizes negation by attaching -ttenne to the verb following the person and number marker. In ellipsis, the morpheme -kka is suffixed to the pronouns or nominal elements for representing all other elements of the antecedent clause omitted in both affirmatives and negatives.